Mixed Cooperation MAC Protocol with Sleep Mechanism for Data Acquisition in Wireless Machine-to-Machine Networks. (22nd October 2013) - Zhao, Yulei; Du, Bing; Ge, Ning
Abstract : By exploring the idle state of each sensor node, a mixed sleep-cooperative time division multiple access (TDMA) media access control (MAC) protocol (MS-CTDMA) is proposed for the wireless data gathering network in wireless machine-to-machine (M2M) networks. The basic idea is that in the idle state, each sensor node dynamically goes into sleep state or cooperative state to maximize the network lifetime. A single-hop network delay model of MS-CTDMA is established by the M X / G / 1 N -policy queue with multiple exhaustive vacations, which provides a way to balance energy consumption in network and the delay of each node with the delay sensitive traffic constraint. Furthermore, based on some reasonable assumptions, the proposed MS-CTDMA analysis model can be extended to the whole M2M network. Consequently, we propose an optimal source node selection strategy from the perspective of the relay node during its idle time, regarding the traffic load, residual energy, and channel state. Numerical results reveal that with proper tradeoff between delays and energy conservations, MS-CTDMA can significantly prolong the network lifetime in Rayleigh fading channels compared to pure sleep scheme.